Echocardiography-Derived Forward Left Ventricular Output Improves Risk Prediction in Systolic Heart Failure - Gentile, Francesco; Sciarrone, Paolo; Panichella, Giorgia; Bazan, Lorenzo; Chubuchny, Vladyslav; Buoncristiani, Francesco; Gasparini, Simone; Taddei, Claudia; Poggianti, Elisa; Fabiani, Iacopo; Aimo, Alberto; Petersen, Christina; et al. (Journal of the American Society of Echocardiography, 2024)
Although it is widely used to classify patients with heart failure (HF), the prognostic role of left ventricular ejection fraction (LVEF) is debated. The aim of this study was to test the hypothesis that echocardiographic measures of forward left ventricular (LV) output, being more representative of cardiac hemodynamics, might improve risk prediction in a large cohort of patients with HF with systolic dysfunction.BACKGROUNDAlthough it is widely used to classify patients with heart failure (HF), the prognostic role of left ventricular ejection fraction (LVEF) is debated. The aim of this study was to test the hypothesis that echocardiographic measures of forward left ventricular (LV) output, being more representative of cardiac hemodynamics, might improve risk prediction in a large cohort of patients with HF with systolic dysfunction.Consecutive stable patients with HF with LVEF <50% on guideline-recommended therapies undergoing echocardiography including the evaluation of forward LV output (i.e., LV outflow tract [LVOT] velocity-time integral [VTI], stroke volume index [SVi], and cardiac index) over a 6-year period were selected and followed for the end point of cardiac and all-cause death.METHODSConsecutive stable patients with HF with LVEF <50% on guideline-recommended therapies undergoing echocardiography including the evaluation of forward LV output (i.e., LV outflow tract [LVOT] velocity-time integral [VTI], stroke volume index [SVi], and cardiac index) over a 6-year period were selected and followed for the end point of cardiac and all-cause death.Among the 1,509 patients analyzed (mean age, 71 ± 12 years; 75% men; mean LVEF, 35 ± 9%), 328 (22%) died during a median follow-up period of 28 months (interquartile range, 14-40 months), 165 (11%) of cardiac causes. On multivariable regression analysis, LVOT VTI (P < .001), SVi (P < .001), and cardiac index (P < .001), but not LVEF (P > .05), predicted cardiac and all-cause death. The optimal prognostic cutoffs for LVOT VTI, SVi, and cardiac index were 15 cm, 38 mL/m2, and 2 L/min/m2, respectively. Adding each of these measures to a multivariable risk model (including clinical, biohumoral, and echocardiographic markers) improved risk prediction (P < .001). Among the different measures of forward LV output, cardiac index was less accurate than LVOT VTI and SVi.RESULTSAmong the 1,509 patients analyzed (mean age, 71 ± 12 years; 75% men; mean LVEF, 35 ± 9%), 328 (22%) died during a median follow-up period of 28 months (interquartile range, 14-40 months), 165 (11%) of cardiac causes. On multivariable regression analysis, LVOT VTI (P < .001), SVi (P < .001), and cardiac index (P < .001), but not LVEF (P > .05), predicted cardiac and all-cause death. The optimal prognostic cutoffs for LVOT VTI, SVi, and cardiac index were 15 cm, 38 mL/m2, and 2 L/min/m2, respectively. Adding each of these measures to a multivariable risk model (including clinical, biohumoral, and echocardiographic markers) improved risk prediction (P < .001). Among the different measures of forward LV output, cardiac index was less accurate than LVOT VTI and SVi.The echocardiographic evaluation of forward LV output improves risk prediction in patients with HF across a wide LVEF spectrum over other well-established clinical, biohumoral, and echocardiographic prognostic markers.CONCLUSIONSThe echocardiographic evaluation of forward LV output improves risk prediction in patients with HF across a wide LVEF spectrum over other well-established clinical, biohumoral, and echocardiographic prognostic markers.